PERAN ULAMA SEBAGAI RESOLUSI KONFLIK CAROK DI DESA KALIBOTO KIDUL KECAMATAN JATIROTO LUMAJANG - Abdul Ghofur (Institut Agama Islam Syarifuddin Lumajang, 2019)
Violence cannot be separated from the role of humans as the perpetrators. One of the many cultural activities owned by Madurese tribe in Kaliboto Kidul, Jatiroto, Lumajang is carok, a deeply rooted culture that has become a tradition. Inspired by A Latief Wiyata's thoughts, the problem that will be raised in this research is how the role of local ulama to resolve such problem. This study employs qualitative research with a descriptive approach. Its orientation is to understand the meaning of the indications and phenomena that occur in Kaliboto Kidul, Jatiroto, Lumajang. In the process of retrieving data, researchers uses observation, interview and documentation techniques. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of the study shows that carok in this area is described as an attempt to kill each other which is committed by men using sharp weapons in the form of celurit. The causing issues are self-esteem harassment, inheritance and revenge actions. Key words: Ulama, Carok, and Criminal Law